Advanced Reliability Modeling 2004
DOI: 10.1142/9789812702685_0010
|View full text |Cite
|
Sign up to set email alerts
|

Determining Optimal Warranty Periods From the Seller’s Perspective and Optimal Out-of-Warranty Replacement Age From the Buyer’s Perspective

Abstract: This paper considers a general repairable product sold under a failure-free renewing warranty agreement. In the case of a general repairable model, there can be two types of failure: type I failure (a minor failure), which can be rectified by minimal repairs; and type II failure (a catastrophic failure), which can be removed only by replacement. After a minimal repair, the product is operational but the failure rate of the product remains unchanged. The aim of this paper is to determine the optimal warranty pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Reliability is an essential feature determining the commercial success of a product and it is a signifi cant element in the competitive strategy of the enterprise (Sander and Brombacher, 2000;Murthy and Djamaludin, 2002;Murthy, 2006;Murthy, 2007;Fabisiak, 2013a, 2013b;Ojurović et al, 2013). It is of importance both for furniture producers (Vickery et al, 1997) and consumers (Udell and Anderson, 1968;Sinclair and Hansen, 1993;Pakarinen and Asikainen, 2001; Ratnasingam, 2003;Chien et al, 2005;Knauf, 2015). Numerous authors point out that quality is particularly demanded on wood products market (Schubert, 1979; Kozak and Maness, 2003).…”
Section: Uvodmentioning
confidence: 99%
“…Reliability is an essential feature determining the commercial success of a product and it is a signifi cant element in the competitive strategy of the enterprise (Sander and Brombacher, 2000;Murthy and Djamaludin, 2002;Murthy, 2006;Murthy, 2007;Fabisiak, 2013a, 2013b;Ojurović et al, 2013). It is of importance both for furniture producers (Vickery et al, 1997) and consumers (Udell and Anderson, 1968;Sinclair and Hansen, 1993;Pakarinen and Asikainen, 2001; Ratnasingam, 2003;Chien et al, 2005;Knauf, 2015). Numerous authors point out that quality is particularly demanded on wood products market (Schubert, 1979; Kozak and Maness, 2003).…”
Section: Uvodmentioning
confidence: 99%
“…In some industries it has been reported that manufacturers can achieve revenues equivalent to four times their product price from after sales service (Bundschuh and Dezvane 2003;Alexander et al 2002). In addition, after sales services can contribute towards new customer attainment (Chien, SHEU, and CHEN 2005) in markets with severe brand competition and towards customer retention and new product development (Choudhary et al 2011;Kurata and Nam 2013;Saccani, Johansson, and Perona 2007;Gaiardelli, Saccani, and Songini 2007;Cohen and Seungjin Whang 1997). Maintenance support involves cost-sharing arrangements, which include fixed-price and cost-plus contracts (Kim, Cohen, and Netessine 2007).…”
Section: After Sales Servicesmentioning
confidence: 99%
“…From a manufacturer's perspective, the cost of a warranty program must be estimated precisely and its effect on the firm's profitability must be studied (Saleh and Marais 2006). Chien et al (2004) estimated the warranty costs during the life cycle of a product in order to create a fund for warranty reserves. They considered a failure-free non-renewing warranty policy for products with age-dependent minimal repair costs, derived the s-expected warranty costs and warranty reserves, and demonstrated the feasibility of using cost information to determine warranty length (Chien et al 2004) They investigated preventative maintenance warranty policies for repairable products.…”
Section: (13)mentioning
confidence: 99%
“…Chien et al (2004) estimated the warranty costs during the life cycle of a product in order to create a fund for warranty reserves. They considered a failure-free non-renewing warranty policy for products with age-dependent minimal repair costs, derived the s-expected warranty costs and warranty reserves, and demonstrated the feasibility of using cost information to determine warranty length (Chien et al 2004) They investigated preventative maintenance warranty policies for repairable products. When the length of a warranty period was pre-specified, the optimal number of preventive maintenance actions, corresponding maintenance degrees, and the maintenance schedule were jointly determined (Mustofa et al 2015).…”
Section: (13)mentioning
confidence: 99%